Power electronics and instrumentation engineering international conference, PEIE 2010, Kochi, Kerala, India, September 7-9, 2010. proceedings - Das, Vinu V. (Communications in Computer and Information Science, 2010)
This book constitutes the proceedings of the International Conference on Power Electronics and Instrumentation Engineering held in Kochi, Kerala, India, in September 2010.